La pobreza como catalizador de la desigualdad / Poverty as a catalyst for inequality (Islas, 2021)
En este texto se presenta la discusión que genera PauletteDieterlen acerca de las implicaciones al momento de abordar el tema dela pobreza. Se problematiza el concepto de igualdad y justicia, así comolas formulaciones que surgen del campo de la economía. A través de esterecorrido, la intención del artículo es superar las limitantes de la mediciónuniversal de la pobreza que supone la economía y la macroeconomía, através de una visión filosófica como lo es el campo de la ética.This text presents the discussion that Paulette Dieterlen generatesabout the implications when addressing the issue of poverty. Theconcept of equality and justice is problematized, as well as the formulationsthat emerge from the field of economics. Through this journey,the intention of the article is to overcome the limitations of the universalmeasurement of poverty that the economy and macroeconomics entail,through a philosophical vision such as the field of ethics.
Keywords: Paulette Dieterlen; poverty and inequality; universal measurement of poverty; pobreza y desigualdad; medición universal de la pobreza